003 Treatment of Sleep Disordered Breathing with Leptin Loaded Exosomes. (3rd May 2021) - Freire, Carla; Pho, Huy; Ramsey, Jacob; Streeter, Stone; Kojima, Ryo; Berger, Slava; Fleury-Curado, Thomaz; Sokolsky, Marina; Batrakova, Elena; Kabanov, Alexander; Polotsky, Vsevolod
Abstract: Introduction: Obstructive sleep apnea (OSA) is characterized by recurrent periods of upper airway obstruction. The prevalence of OSA exceeds 50% in obese individuals and in 10–20% of obese patients OSA coexists with obesity hypoventilation syndrome (OHS) defined as daytime hypercapnia and hypoventilation during sleep attributed to the depressed control of breathing. There is no effective pharmacotherapy for OSA and OHS. Leptin is a potent respiratory stimulant and a potential therapeutic candidate. However, diet-induced obesity (DIO) results in reduced permeability of the blood-brain barrier (BBB) for leptin. Previous studies have shown that the BBB can be penetrated by exosomes, natural nanoparticles that can be used as drug delivery vehicles. In this study, we aimed to determine if exosomes overcome the BBB and treat OSA and OHS in DIO mice. Methods: o examine the ability of exosomes to cross the BBB, male, lean (n=5) and DIO (n=5) C57BL/6J mice were injected with fluorescent exosomes or saline into the lateral tail vein. After 4h fluorescent exosomes biodistribution was evaluated by an in vitro imaging system (IVIS). Saline injected mice images were used for background adjustment. A separate subgroup of male, DIO (n=10) and lean (n=10) mice were headmounted with EEG and nuchal EMG leads. Sleep studies were performed in a plethysmography chamber and mice received saline, empty exosomes, free leptin, or leptin-loaded exosomes in a crossover manner. Results: Exosomes were successfully delivered to the brain and the transport across the BBB was more efficient in DIO mice with 2-times greater relative fluorescence units measured in DIO when compared to lean mice (p<0.005). In DIO mice, exosomal leptin induced dramatic 1.7-2.2-fold increases in minute ventilation and 1.5-2.0-fold increases in maximal inspiratory flow during both flow-limited (upper airway/sleep apnea) and non-flow limited breathing (control of breathing) (p<0.05). In contrast, free leptin had no effect. Lean mice did not present significant sleep disordered breathing and no differences were observed between groups. Conclusion: We demonstrated that exosomes overcome the BBB and that leptin-loaded exosomes treat OSA and OHS in DIO mice. Support (if any): R01HL 128970, R01HL 138932, R61 HL156240, U18 DA052301, FAPESP 2018/08758-3